Measurements of enteral feeding intolerance in critically ill children: a scoping review - Li, Yan; Fu, Cong-Hui; Ju, Min-Jie; Liu, Ji; Yang, Xiao-Ya; Xu, Ting-Ting (Frontiers in Pediatrics, 2024)
Objective: To examine the measurements on enteral feeding intolerance (EFI) in critically ill children.Methods: The Joanna Briggs Institute methods for conducting a scoping review were followed.Articles published since 2004 which assessed EFI in critically ill children were identified. A full search strategy was executed in seven English databases (MEDLINE, EMBASE, PubMed, Web of Science, Cochrane Central Register of Controlled Trials, JBI EBP, CINAHL) and four Chinese databases (CNKI, VIP, Wanfang, Sinomed). Two reviewers screened records according to our inclusion and exclusion criteria, and conducted a full-text review of selected articles. The reference lists of all studied selected were screened for additional sources. Relevant data was extracted using a researcher-developed tool.Results: Of the 627 articles identified, 32 were included in this scoping review. Most articles focused on the measurement of high gastric residual volume (n=22), followed by diarrhea (n=20), and vomiting (n=9). Most of the studies were of observational-analytic design (13/32) and experimental design (8/32).Conclusion: This scoping review addressed the complexity and diversity of EFI measurements.Given the importance of adequacy of enteral nutrient intake, we highlighted the necessary to develop individual measurements of EFI, taking the age of children and disease condition into consideration. Further studies can also investigate accurate and objective physiological measurements of EFI to advance EN and improve outcomes in critically ill children.